How Brand Personality, Shopping Lifestyle, and Hedonic Motives Influence Impulse Buying Through Positive Emotions - Septian Sutrisno Adi Nugroho; Muhammad Sholahuddin (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research explores the extent to which brand character, consumer-oriented lifestyle patterns, and pleasure-seeking purchasing tendencies contribute to spontaneous buying behavior, while considering favorable emotional states as an intervening mechanism among shoppers at Outlet Biru Yogyakarta. Within today's retail landscape, where experiential value increasingly outweighs functional considerations, unplanned purchase decisions frequently emerge from affective responses and lifestyle-driven consumption orientations. This research adopted an explanatory quantitative approach involving 150 participants chosen through purposive sampling techniques. Data collection relied on a five-point Likert questionnaire, and analysis was conducted in SmartPLS using evaluation of measurement models, assessment of structural models, and mediation testing. Findings reveal that brand personality together with hedonic shopping significantly enhance impulse buying, whereas shopping lifestyle fails to produce a statistically significant effect outcome observed. Moreover, positive emotion does not serve as a mediating variable linking brand personality, shopping lifestyle, hedonic shopping, and impulse buying relationships. This study's novelty is established by showing that positive emotion does not consistently operate as a mediating mechanism within hedonic retail contexts framework. Research contributes to consumer behaviour literature by indicating that hedonic and brand-related determinants can directly trigger impulse buying behavior , offering practical insights for retail managers to strengthen experiential shopping strategies.